Sitotoksisitas Ekstrak Metanol Daun Sukun (Artocarpus altilis), Nangka (Artocarpus heterophyllus), dan Kluwih (Artocarpus camansi) Terhadap Sel Kanker Payudara T47D - Gustina, Vindhy Mulya, Dr. Haryoto, M.Sc (2016)
Cancer in Indonesia almost 70% were found in the late stage. One of them breast cancer is becoming an important issue in the world of health. Plant groups of Artocarpus such as breadfruit, jackfruit, and kluwih on the leaves have cytotoxic activity with IC50 values that potent in certain cancer cells such as MCF-7 (breast cancer), SW-480 (lung cancer), and SMMC -7721 (liver cancer). The study encourages research about whether or not the cytotoxic activity of the leaves of breadfruit, jackfruit, and kluwih against breast cancer cells T47D with IC50 values are calculated. Extraction using maceration method with methanol. Identification of the content of each plant using Thin Layer Chromatography with ethyl acetate: n-hexane (2: 8). The method for testing the cytotoxic activity is MTT assay with a series of concentrations of each extract 1000, 500, 250, 125 and 62.5 µg/mL. Absorbance is obtained from the MTT assay results that read by ELISA reader at a wavelength of 595 nm and calculated % sel hidup cells to obtain IC50 values. The test results of phytochemical screening by TLC showed that all three plants contain flavonoid compounds, alkaloids, and tannins. Based on the test cytotoxic activity of the methanol extract of leaves of breadfruit, jackfruit, and kluwih showed that this extract had low activity against cancer cells T47D with IC50 values respectively 234.4; 891.2;and 239.8 µg/mL.